Aramaic Daniel: a textual reconstruction of chapters 1-7 - Suchard, Benjamin (Studia Semitica Neerlandica, 2022)
This book investigates the literary and textual development of the book of Daniel, especially the six court tales and the Four Beasts apocalypse, based on comparison of ancient manuscripts and versions and internal reconstruction